Physicochemical and Functional Properties of Chemically Pretreated Ndou Sweet Potato Flour - Khuthadzo Ngoma; Mpho E. Mashau; Henry Silungwe (International Journal of Food Science)
Sweet potato (Ipomoea batatas Lam) is a nutritious crop abundant in calories and bioactive compounds such as beta-carotene, ascorbic acid, polyphenols, and dietary fibre. This study investigated the effect of pretreatments on the physicochemical and functional properties of Ndou sweet potato (NSP) flour. Flour samples were prepared by randomly assigning NSP slices to two treatments (citric acid and sodium metabisulphite) at 5, 10, and 15 g/L concentration for 10 min. Distilled water was used as control. The moisture content (7.70%) of NSP flour treated with citric acid was significantly (p<0.05) higher than that of the flour treated with sodium metabisulphite (5.54%) as the concentration level increased. The treatments did not significantly (p<0.05) affect the protein and fat contents of the NSP flour and protein increased from 2.54 to 2.82%, while fat decreased from 0.69 to 0.61%. Sodium metabisulphite treated samples had a higher L∗ value, ash, and pH level than citric acid treated samples. However, pH was slightly decreased by both treatments from 6.05 to 5.09. Citric acid treated samples had higher a∗ and b∗ values than sodium metabisulphite treated samples. In terms of the functional properties of NSP flour, the treatments significantly (p<0.05) affected the water absorption capacity, viscosity, swelling power, solubility index, and thermal properties although the bulk density and least gelation concentration were not significantly (p>0.05) affected. Sodium metabisulphite was very effective in improving physicochemical and functional properties of NSP flour as compared to citric acid. The findings of this study show the possibilities of using NSP flour in food systems as gelling agent, fat replacer, and thickeners.